Dynamics of an Anisotropic Metaphosphate LiNaKCsPO3 Glass by Inelastic X‐Ray Scattering. Issue 11 (10th July 2020) - Hosokawa, Shinya; Inaba, Seiji; Uchiyama, Hiroshi; Tsutsui, Satoshi
Abstract : To clarify the mechanism of the entropic shrinkage of a metaphosphate LiNaKCsPO3 glass, high‐resolution inelastic X‐ray scattering is carried out in the momentum transfer ( Q ) range from 1.6 to 15.9 nm −1 by changing the stretched sample rod directions perpendicular and parallel to the X‐ray scattering plane. Phonon excitations are found only in a low Q range below about 3 nm −1, and the so‐called Boson peaks are observed in the Q region beyond 5.6 nm −1 . These excitations exhibit mostly no differences in the rod direction. A spectral enhancement at the prepeak position in the total X‐ray scattering spectrum is due to the quasielastic contributions. The direction difference in the width of the quasielastic peak becomes largely broadened near the prepeak region, which may be owing to a low excitation energy of the phosphate chains across the chain direction. Abstract : Metaphosphate LiNaKCsPO3 glass is the first inorganic material that shows an entropic shrinkage phenomenon like an organic rubber. Inelastic X‐ray scattering to study the anisotropy of this glass exhibits a large difference in the quasielastic range between the scattering directions, which is related to micro‐Brownian motions of elongated phosphate chains as predicted for the origin of entropic shrinkage.